PETROLOGY OF PLAGIOGRANITES OF THE YENISEI BATHOLITH, WESTERN SAYAN - Grebenshchikova V.I.; Koval P.V. (My University, 2006)
The tonalite-plagiogranite (tonalite-trondhjemite) association only occasionally occurs in the form of large granitoid bodies, such as the Yenisei Batholith (>500 km2 in area). The granitoids of the Yenisei Batholith belong to Na-rich tholeiitic rock series and differ from granitoids of the calc-alkaline series in having lower contents of alkalis and alumina (12-14 wt % Al2O3) and low contents of granitophile elements (Rb, Li, Cs, Be, Nb, Ta, and W), Cr, and Ni. The Cr/V (<0.10) and Rb/Sr (0.01-0.1) ratios of these rocks are at a minimum, and their K/Rb (600-1000) and Na/K (5-10) ratios are at a maximum compared to those of the rocks of the most widely spread granitoid batholiths. The plagiogranites typically have REE concentrations higher than those in oceanic plagiogranites and display weakly fractionated REE patterns (La/Yb = 1.4-3.4) with weak (or without) Eu anomalies. The lower initial Sr ratios of these rocks (0.704) and their relatively high concentrations of Pb, Zr, and B testify to the predominantly mantle provenance of their protolithic material. Geological and geochemical characteristics of the Yenisei pluton suggest that its genesis can be considered within the scope of the model of retrograde-type magmatic replacement and that the batholith was produces by the earliest granitization processes in the oceanic crust. The granitic melt was derived at low pressures (<5 kbar) and intermediate temperatures (~00°C), at the inflow of an aqueous transmagmatic fluid into the magma-generating area and the subsequent fluid-magmatic differentiation. Considering the volumes and compositions of rocks composing the Yenisei Batholith, the latter can be attributed, similarly to other typical granitoid batholiths, to crustal plutons, which differ from both oceanic plagiogranites in ophiolitic belts and continental trondhjemites. The rocks can be regarded as an individual geochemical type of crustal plagiogranites. © 2006 Nauka/Interperiodica.